Observation of the [xi]-b→J/[psi][lambda]K− decay - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2017)
The observation of the decay Ξb−→J/ψΛK− is reported, using a data sample corresponding to an integrated luminosity of 3fb−1, collected by the LHCb detector in pp collisions at centre-of-mass energies of 7 and 8TeV. The production rate of Ξb− baryons detected in the decay Ξb−→J/ψΛK− is measured relative to that of Λb0 baryons using the decay Λb0→J/ψΛ. Integrated over the b-baryon transverse momentum pT<25GeV/c and rapidity 2.0<y<4.5, the measured ratio isfΞb−fΛb0B(Ξb−→J/ψΛK−)B(Λb0→J/ψΛ)=(4.19±0.29 (stat)±0.15 (syst))×10−2, where fΞb− and fΛb0 are the fragmentation fractions of b→Ξb− and b→Λb0 transitions, and B represents the branching fraction of the corresponding b-baryon decay. The mass difference between Ξb− and Λb0 baryons is measured to beM(Ξb−)−M(Λb0)=177.08±0.47 (stat)±0.16 (syst)MeV/c2.